A Direct Investment Method of Closed Two-Piece Hollow Bulb Obturator - Suryakant C. Deogade; Sneha S. Mantri; Dinesh Naitam; Gunjan Dube; Pushkar Gupta; Ashish Dewangan (Hindawi Limited, 2013)
Maxillary defects occur due to surgical treatment of benign and malignant tumors, congenital malformation, and trauma. Prosthetic rehabilitation in such patients is influenced by the size and location of the defect. The most common of all intraoral defects are seen in the maxilla, in the form of an opening into the maxillary sinus and nasopharynx. These defects create disabilities in speech, deglutition, and mastication. The prosthesis which closes such an opening and recreates the functional separation of the oral cavity and sinus and nasal cavities is referred to as an obturator. Numerous techniques of hollow bulb fabrication have been mentioned in the literature from time to time. But there are only a few methods for bulb fabrication in two-piece obturator. This technique describes a direct investment method of waxed-up closed hollow bulb two-piece obturator.